Meta-analysis of venous anastomosis techniques in free flap reconstruction - Geierlehner, Alexander; Rodi, Timo; Mosahebi, A.; Tanos, G.; Wormald, J. C. R. (Journal of plastic, reconstructive & aesthetic surgery, 2020)
Background - Coupler devices and hand-sewn anastomosis techniques are both routinely employed for venous anastomosis in microsurgical free flap transfer. However, uncertainty remains about whether those two techniques are different in terms of risk of venous thrombosis. The aim of this review was to evaluate the quality of the evidence and quantify the difference in venous thrombosis rates in both techniques. - Method - A Preferred Reporting Items for Systematic Reviews and Meta-Analyses compliant systematic review and meta-analysis were performed according to a previously published protocol. MEDLINE and Embase databases were searched from inception to 1 October 2018. Clinical studies using coupler devices for venous anastomoses in free tissue transfer were included. The primary outcome was post-operative venous thrombosis risk. Surgical anastomosis time was a secondary outcome. The risk of bias was assessed with the ROBINS-I or NIH tool and recommendations were made using the GRADE criteria. - Results - A total of 10,851 patients across 32 observational retrospective studies were included, with data available for 12,769 free flaps in breast, head and neck, limb and other reconstructions. Direct comparison meta-analysis of 7 studies showed a reduced post-operative thrombosis risk for venous coupler, although this was an imprecise estimate (RR 0.68 [95% CI 0.39-1.19]). The risk of bias was consistently high across all studies. - Conclusion - Venous couplers may reduce the risk of venous thrombosis, but further randomised trial data are needed to improve the accuracy of this estimate. Further research should also assess size-mismatch between donor and recipient vessel, and the influence of coupler size on outcomes (PROSPERO registration ID: CRD42018110111).
Available online 29 November 2019
Gesehen am 14.04.2020